# Exponential Function

i'm having problems with two questions. Please help me! Thanks! i've tried everything but i can't solve them...

1) Solve: (3/4)^3x-2 * (4/3)^1-x = 9/16

2) Solve for x : 3(3^x) + 9(3^-x)=28

## Answers and Replies

Related Introductory Physics Homework Help News on Phys.org
Tom Mattson
Staff Emeritus
Science Advisor
Gold Member
Could you please show us what you've tried?

Well for no. 1 this is what i've tried but i keep getting the wrong answer:
*2nd step* 3^3x-2/ (2^2)^3x-2 * (2^2)^1-x/3^1-x = 9/16
3^3x-2/2^6x-4 * 2^2-2x^3^1-x = 9/16
2^-8x+6/3^-4x+3 = 3^2/2^4
Therefore, -8x+6/-4x+3 = 1/2
-16x +12 = -4x +3
-12x = -9
x = 3/4
*the answer was 5/4*

and for no.2 i have no idea what my next step is...

Tom Mattson
Staff Emeritus
Science Advisor
Gold Member
There's a much easier way.

First, recognize that $\frac{4}{3}=(\frac{3}{4})^{-1}$ and that $\frac{9}{16}=(\frac{3}{4})^2$.

Once you do that, all the bases will be the same. Then you can apply the rule $a^xa^y=a^{x+y}$ to simplify the left side, and then solve the equation.

You'll want to do something similar to reduce the left side of #2 to a single term.

I'm trying to follow your work, but it's very difficult to read.

Here is your second step in Latex form. Maybe you could rewrite the next steps.

$$\frac{3^{3x-2}}{(2^2)^{3x-2}}*\frac{(2^2)^{1-x}}{3^{1-x}}$$

yeah, sure, ill try. Then ill let you know

i tried it but i keep eliminating my variable

Tom Mattson
Staff Emeritus
Science Advisor
Gold Member
love_joyously said:
i tried it but i keep eliminating my variable
How? When you add the exponents, the variable does not cancel out.

ok.. well this is what i did:

3^3x-2/2^6x-4 * 3^x-1/2^2x-2 = 3^2/2^4
3^4x-3/2^8x-6=3^2/2^4
Therefore, 4x-3/8x-3 = 1/2
*cross-multiply* 8x-6 = 8x-6
0=0

?????

Tom Mattson
Staff Emeritus
Science Advisor
Gold Member
love_joyously said:
Therefore, 4x-3/8x-3 = 1/2
This step is wrong.

You'll have better luck if you don't use different exponents for the numerator and denominator.

$$\left(\frac{3}{4}\right)^{3x-2}\left(\frac{3}{4}\right)^{x-1}=\left(\frac{3}{4}\right)^2$$

Now you can simply add the exponents on the left side, and solve for x.

ook.. i get : (3/4)^4x-3 = (3/4)^2

wat now?

Tom Mattson
Staff Emeritus
Science Advisor
Gold Member
See how the bases are equal? That means that the exponents must be equal in order for the equation to hold. Set them equal, then solve for x.

love_joyously said:
ook.. i get : (3/4)^4x-3 = (3/4)^2

wat now?
I know know this problem,
4x-3=2
then x=5/4

oh..ok!!! now i get it.. thanks!

so for no. 2, what do u suggest me do?

let t=3^x then Solve for t : 3t^2 -28t + 9=0
Yeah..

Tom Mattson
Staff Emeritus
Science Advisor
Gold Member
djeipa said:
let t=3^x then Solve for t : 3t^2 -28t + 9=0
Yeah..
That's what I would do, too. Solve that quadratic equation, then solve for x.

Ouabache
Science Advisor
Homework Helper
love_joyously said:
2) Solve for x : 3(3^x) + 9(3^-x)=28
I was trying to follow what you did to arrive at the quadratic expression.
It seems you multiplied the original equation by $3^x$

$3^x [ {3(3^x)+9(3^{-x})=28}]$

$3(3^x)^2 +9 = 28(3^x)$

$3(3^x)^2 -28(3^x) +9 = 0$

And If $t = 3^x$ then $3t^2-28t+9=0$

With a bit of http://www.deephousepage.com/smilies/OLA.gif [Broken] I get, x = -1, 2

Last edited by a moderator: